Використання технології ДЗЗ та ГIС для контролю видобування корисних копалин Хмельницької області - Шумейко, В.О. (Екологічна безпека та природокористування, 2009)
By technology of the remote sensing of Earth and possibilities of the geographic information systems the bases of these existent deposits of natural minerals and providing of the effective monitoring are created.